The paradoxical effects of high involvement work practices on employees and service outcomes: a trichromatic perspective - Yang, Xiaoxi; Qadir, Alia; Shahid, Bilal; Tahir, Safdar Husain (Frontiers in Psychology, 2024)
This research delves into the complex impact of High Involvement Work Practices (HIWPs) on various facets of employee well-being and service outcomes within the framework of the trichromatic service conception. Utilizing the Job Demands-Resources (JD-R) model, the study uncovers the dual, both beneficial and detrimental, effects of HIWPs on service performance, work–family conflict, subjective well-being, and work-family enrichment. Examining the conflicting paths of job demands (workload) and job resources (customer orientation), the analysis incorporates the moderating influence of a strategic contextual factor—supervisor support. Data was collected through self-administered questionnaires from 475 respondents in Pakistani banks, and the analysis employed moderated mediation analysis using SPSS, AMOS, and the PROCESS Macro. All proposed hypotheses received support. The results indicate that HIWPs enhance service performance by promoting customer orientation but concurrently escalate workload, leading to adverse consequences for subjective well-being and work–family conflict. The study underscores the importance of implementing HIWPs under supportive leadership to maximize positive outcomes and mitigate negative consequences. Ultimately, this approach enables employees to effectively serve customers, maintain a healthy work-family balance, and contribute to the long-term growth and sustainability of organizations.